2019
DOI: 10.1159/000501985
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and Cultural Determinants of Interest and Uptake of Skin Cancer Genetic Testing in Diverse Primary Care

Abstract: <b><i>Background:</i></b> Translational research in genomics has limited reach and requires efforts to broaden access and utility in diverse populations. Skin cancer is common and rates are rising, including among Hispanics. Germline variants in the melanocortin-1 receptor (<i>MC1R</i>) gene are common in the population and confer moderate risk for melanoma and basal cell cancers across skin types. Feedback about <i>MC1R</i> risk status may promote skin cancer ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 52 publications
2
14
1
Order By: Relevance
“…This may include large portions of the general population who tan and/or do not use adequate sun protection [76]. In the current study, patients with low risk perceptions were significantly more likely to refuse study participation than those with higher risk perception [54], which may have decreased the ability to detect an overall impact of the genetic testing feedback. It is an important element of study rigor that we were able to well-characterize these study refusers.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This may include large portions of the general population who tan and/or do not use adequate sun protection [76]. In the current study, patients with low risk perceptions were significantly more likely to refuse study participation than those with higher risk perception [54], which may have decreased the ability to detect an overall impact of the genetic testing feedback. It is an important element of study rigor that we were able to well-characterize these study refusers.…”
Section: Discussionmentioning
confidence: 68%
“…Further, those with higher perceived skin cancer risk and those with greater interest in learning about genes were more likely to participate. Participants who answered "don't know" to absolute perceived skin cancer risk were less likely to participate in the study than patients who gave another scale response; these psychosocial factors remained significant predictors of study participation after adjustment for ethnicity and education [54].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Comprehension was assessed by providing a short passage about genetics and skin cancer risk, which was created for a young adult population. We chose this topic since it is likely unfamiliar to young adults 22,23 so we could better assess knowledge learned from the passage. Five items were included to assess comprehension, with true, false, or unsure response options.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, individuals who, between 1993 and 2000, indicated that they did not know their risk of having HIV were less likely to obtain an HIV test than those who provided a scale response (Kiviniemi et al, 2018). In addition, DK responding (compared with a scaled response) to items assessing perceived risk of skin cancer was associated with lower likelihood of enrolling in a research study that provided information about the risk of skin cancer (Hay et al, 2019). Furthermore, participants who indicated that they were uncertain about their perceived risk had lower odds of eating a healthy diet or engaging in physical activity in the past 12 months, regardless of the level of perceived risk they indicated (Orom et al, 2020).…”
Section: Importance Of Perceived Risk For Behavioral Engagementmentioning
confidence: 99%